The Dynamics of Family Communication among Working Mothers in the Digital Era - Satia Rahmawati, Lusi; Hidayat, Dasrun; Rina, Nofha; Nurhadi, Zikri Fachrul (UPT Publikasi Ilmiah UNISBA, 2024)
In this modern age, most families have both parents working. Despite their professional responsibilities, mothers play a crucial role in the family’s health and well-being, particularly as the primary educators of their children. This research aims to analyze the experiences of working mothers regarding family communication dynamics through WhatsApp, focusing on the closeness between working mothers and their children. The study employs qualitative methods with a phenomenological approach to explore the shared experiences of individuals or groups with similar characteristics. The participants are working mothers aged 27 or older, with at least a diploma education, who actively use WhatsApp to communicate with their children and reside in Bandung. The research indicates that WhatsApp is a highly effective communication tool for working mothers to sustain family communication dynamics. It helps instill positive values, sympathy, and empathy, and is considered a primary necessity for maintaining a close relationship between working mothers and their children.